Room temperature ferromagnetism in Zn1−xNixO nanostructures synthesized by chemical precipitation method. (24th October 2017) - Chacko, Levna; Shafeeq, K M; Anjana, R; Jayaraj, M K; Aneesh, P M
Abstract: ZnO nanomaterials have drawn considerable research interest as a multifunctional semiconductor material due to its unique thermal, electrical, optical and optoelectronic properties and also a suitable candidate for the transparent conducting oxide (TCO) layer in optoelectronic devices. The present work deals with the co-precipitation synthesis of ZnO nanostructures with Ni dopants. The structure and phase identification, morphology, optical and magnetic response of the prepared Zn1− x Ni x O nanostructures have been investigated by employing x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive x-ray spectroscopy (EDAX), Raman analysis, UV–Vis–NIR and fluorescence spectrophotometer and vibrating sample magnetometer (VSM) measurements. Structural studies reveal the hexagonal wurtzite structure of ZnO nanostructures with a slight decrease in the particle size with Ni doping. The incorporation Ni in the ZnO host lattice is confirmed by EDAX measurements. Optical studies confirm the observance of blue shift and violet photoluminescence emission for Zn1− x Ni x O nanostructures. Vibrating sample magnetometer (VSM) measurements of Zn1− x Ni x O nanostructures shows hysteresis loop at room temperature confirming the ferromagnetic behaviour of the samples.